Electrochemical bicarbonate reduction in the presence of Diisopropylamine on sliver oxide in alkaline sodium bicarbonate medium - Hosseini, Soraya; Moghaddas, Houyar; Masoudi Soltani, Salman; Aroua, Mohamed Kheireddine; Kheawhom, Soorathep; Yusoff, Rozita (Elsevier, 2018)
In this study, the reduction of bicarbonate in the presence four amines on a silver oxide/ carbon nanotube (Ag2O/CNT) composite electrode has been investigated. The studied amines includes ethanolamine (MEA), diethylenetriamine (DETA), diisopropylamine (DIPA) and aminoethylpiperazine (AEP). Regardless of amine type, in the absence of a bicarbonate solution, no reduction/oxidation peaks were observed. However, in the presence of bicarbonate, a single reduction peak along with simultaneous H2 evolution was clearly observed. The cyclic voltammetry measurements showed that only diisopropylamine (DIPA) had a significant catalytic effect toward bicarbonate reduction on the composite electrode. No peak was observed in the anodic direction of the reverse scans, suggesting the irreversible nature of the electrochemical process. The effect of scan rate revealed that the irreversible reduction mechanism is governed by both diffusion and adsorption pathways. In addition of carbonate ions, format ions also have been detected in liquid phase. In order to study the mechanism of bicarbonate reduction in the DIPA solution on Ag2O/CNT electrode, electrochemical impedance spectroscopy (EIS) was employed. The EIS results showed that the charge transfer resistance decreased when the potential decreased from -0.1 to -0.9 V then faded with a further rise in potential to up to -1.9 V. In addition, an inductive loop under certain conditions was observed in the complex plane due to the formation of adsorbed intermediates onto the electrode surface.